The clinical application of flexible bronchoscopy in a neonatal intensive care unit - Ke, Li-qin; Shi, Ming-jie; Zhang, Fei-zhou; Wu, Hu-jun; Wu, Lei; Tang, Lan-fang (Frontiers in Pediatrics, 2022)
Abstract: Objective: Flexible bronchoscopy is widely used in infants and plays a crucial role. The study aimed to investigate the value and clinical safety of flexible bronchoscopy in a neonatal intensive care unit. Methods: A retrospective analysis was performed on the clinical data of 116 neonates undergoing who underwent flexible bronchoscopy and the outcomes of 147 procedures of results were enrolled. Correlation analysis was performed on the relationship between flexible bronchoscopy findings, microscopic indications and clinical disease. Results: The 147 procedures performed were due to the following reasons: problems related to artificial airways,58 cases (39.45%);upper respiratory problems,60 cases (40.81%) (recurrent dyspnea,23 cases; upper airway obstruction,17 cases; recurrent stridor,14 cases; hoarseness, six cases),lower respiratory problems, 51 cases (34.69%) (persistent pneumonia, 21 cases; suspicious airway anatomical disease, 21 cases; recurrent atelectasis, eight cases; pneumorrhagia, one case),feeding difficulty three cases(2.04%). The 147 of endoscopic examinations were performed due to the following reasons: pathological changes,141cases (95.92%);laryngomalacia,[78 cases (53.06%)];mucosal inflammation/secretions,[64 cases (43.54%)];vocal cord paralysis, [29 cases (19.72%)];trachea/bronchus stenosis [17cases (11.56%)]; [ five cases of congenital annular constriction of trachea, seven cases of left main tracheal stenosis, one case of the right middle bronchus stenosis, two cases of tracheal compression, and two cases of congenital tracheal stenosis];subglottic lesions, 15 cases [10.20%] [ eight cases of subglottic granulation tissue, six cases of subglottic stenosis, one cases of subglottic hemangioma];tracheomalacia, 14 cases [9.52%]; laryngeal edema, five cases [3.40%];tracheoesophageal fistula, four cases [2.72%];rhinostenosis, three case [2.04%];tracheal bronchus, three case [2.04%];glossoptosis, 2 case [1.36%]; laryngeal cyst, 2 case [1.36%];laryngeal cleft, 2 case [1.36%];tongue base cysts, one case [0.68%];pneumorrhagia, one case [0.68%]; Complications were rare and mild. Conclusion: Flexible bronchoscopy is safe and effective for diagnosing and differentiating neonatal respiratory disorders in neonatal intensive care units.